Possibilities for Investing Foreign Exchange Reserves into Fixed Income Securities - Sinisha Velkovski (National Bank of the Republic of Macedonia, 1998)
When in early seventies and, especially, early eighties, the system of fixed foreign exchange rates fell apart, significant number of central banks in the world tended to place part of the foreign exchange reserves into fixed income securities. The reason for this practice lies in the fact that after the USA Government had suspended dollar convertibility into gold, the role of the dollar as a currency which serves as means for value maintenance, started to decrease. Therefore, the interest in investing in fixed income securities appeared as an alternative solution. These securities, and especially Government fixed income securities, are considered to be very secure placements which on a longer term would bring higher income compared with bank deposits. Also, they are liquid because it is very easy to convert them into cash, and they diversify the credit risk.
Keywords: 330